Cold Induced Antisense Transcription of FLOWERING LOCUS C in Distant Grasses - Jiao, Fuchao; Pahwa, Kanchan; Manning, Murray; Dochy, Niklas; Geuten, Koen (Frontiers in Plant Science, 2019)
Functional conservation of RNAs between different species is a key argument for their importance. While few long non-coding RNAs are conserved at the sequence level, many long non-coding RNAs have been identified that only share a position relative to other genes. It remains largely unknown whether and how these lncRNAs are conserved beyond their position. In Arabidopsis thaliana, the lncRNA COOLAIR is transcribed antisense from FLOWERING LOCUS C (FLC) in response to cold. Despite relatively low sequence similarity, the COOLAIR expression pattern and in vitro RNA secondary structure are highly conserved across the family Brassicaceae, which originated some 50 mya. It is unclear however, whether COOLAIR functions in distantly related species such as monocots, which diverged some 150 mya. Here, we identified antisense lncRNAs from FLC homologs in various monocot species that share no sequence similarity with A.thaliana COOLAIR. Yet similar to COOLAIR, we found that BdODDSOC1 antisense (BdCOOLAIR1) and BdODDSOC2 antisense (BdCOOLAIR2) are induced by cold in a Brachypodium distachyon winter accession. Across B.distachyon accessions, the sequences of BdCOOLAIR1 and BdCOOLAIR2 are less conserved than exons but more conserved than flanking regions, suggesting a function for the transcript itself. Knock down of the BdODDSOC2 non-overlapping BdCOOLAIR2 transcript did not show a morphological phenotype, but did result in significantly higher BdODDSOC2 expression during cold, indicating that BdCOOLAIR2 performs a role in cis in the rate of BdODDSOC2 silencing. This functional similarity between eudicot and monocot species reveals ancient conservation or convergent evolution of FLC antisense transcription. Either scenario supports its functional importance.